2021
DOI: 10.3346/jkms.2021.36.e114
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Events Following Immunization Associated with Coronavirus Disease 2019 Vaccination Reported in the Mobile Vaccine Adverse Events Reporting System

Abstract: Background Vaccination against coronavirus disease 2019 (COVID-19) is underway globally to prevent the infection caused by the severe acute respiratory syndrome coronavirus 2. We aimed to investigate the adverse events following immunization (AEFIs) for COVID-19 among healthcare workers (HCWs). Methods This was a retrospective study of the AEFIs associated with the first dose of the ChAdOx1 nCoV-19 vaccine at the Kosin University Gospel Hospital from March 3 to March 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
57
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 6 publications
14
57
2
2
Order By: Relevance
“…10 A retrospective study from Korea included 994 health care workers who took the ChAdOx1 nCoV-19 vaccine (where the data was collected using mobile vaccine adverse events reporting system), has also shown that the severity of most AEFIs to be mild-to-moderate and the severity of AEFI to be less in older age group. 11 Our study has shown that the severity of AEFI was moderate in intensity in the majority of the population. The chances of moderate AEFI were found to vary with age and sex significantly in binary logistic regression.…”
Section: Discussionmentioning
confidence: 64%
“…10 A retrospective study from Korea included 994 health care workers who took the ChAdOx1 nCoV-19 vaccine (where the data was collected using mobile vaccine adverse events reporting system), has also shown that the severity of most AEFIs to be mild-to-moderate and the severity of AEFI to be less in older age group. 11 Our study has shown that the severity of AEFI was moderate in intensity in the majority of the population. The chances of moderate AEFI were found to vary with age and sex significantly in binary logistic regression.…”
Section: Discussionmentioning
confidence: 64%
“…40 Recently, 3 academic Korean hospitals have reported 2 prospective and 1 retrospective studies with healthcare workers (7,625, 1,483, and 1,503 subjects, respectively) who received COVID-19 vaccines (Pfizer-BioNTech or Oxford-AstraZeneca) via survey or mobile adverse event reporting systems. 41 42 43 These studies suggested that adverse reactions to COVID-19 vaccination with the above 2 vaccines were mostly mild to moderate, and more frequently reported in female, younger age, and Oxford-AstraZeneca vaccinated groups. The drug permission requirement labels endorsed by the Korean Ministry of Food and Drug Safety state that the anaphylaxis risk of the 2 vaccines is unknown (non-assessable).…”
Section: Incidence Of Anaphylaxis To Covid-19 Vaccinesmentioning
confidence: 96%
“…In principle, COVID-19 vaccination includes all subjects without contraindications. 43 46 It is recommended to exclude and delay vaccination if subjects have a current COVID-19 infection or fever ≥ 37.5°C. People who are pregnant or ≤18 years old are also excluded from the vaccination because of a lack of safety and efficacy data.…”
Section: Contraindications To Covid-19 Vaccines In the General Populationmentioning
confidence: 99%
“…Some members of the Korean Society of Emergency Medicine raised concerns that this public anxiety could eventually increase the number of ED visitors and cause difficulties in emergency patient care. However, although many studies of adverse events of vaccinations exist, 4 6 studies on the post-vaccination utilization of the ED are exceedingly rare. Fertel et al's study 8 briefly reported 380 ED visitors (due to reactions to COVID-19 vaccination) over 7 weeks, whereas 70.3% of cases required laboratory work, 61.6% were given intravenous medications, and 17.9% were hospitalized.…”
Section: Discussionmentioning
confidence: 99%
“…Many ED staff members have reported struggling to secure enough quarantine space for the treatment of febrile patients. Importantly, most systemic symptoms of post-vaccination patients resemble COVID-19 symptomatology 4 6 7 ; therefore, if nationwide vaccination begins, additional overcrowding is expected in the EDs. 7 Despite these concerns, studies on the adverse post-vaccination events are being conducted, but studies on these events, specifically within the context of ED utilization, remain scarce.…”
Section: Introductionmentioning
confidence: 99%